Generación de un plan de desarrollo para el Campo Olympus offshore mediante simulación numérica de software libre (OPM) (2018)
The Olympus field is a model of a synthetic deposit allusive to a real field of the North Sea, prepared at the beginning of 2017 between the oil industry and the academy, with the purpose of delivering a challenge to the international academic community. The field has a geologically modeled static and dynamic model, showing 11 geological models, which were elaborated from different petrophysical points of view to evaluate their uncertainties. The main objective of this project is to generate a development plan for the Olympus Offshore Field through numerical simulation in the OPM software, in order to start the productive life of this field through primary and secondary production by injection of water only. Being this an offshore field, three possible cases of drilling will be elaborated and evaluated in the 11 geological models by means of statistics, to determine the best case of drilling and the best geological model that represents the Olympus Field. Thus, based on financial analysis, the best case of drilling and the best geological model is sought, evaluating their potential profits over 20 years by means of the net present value indicator NPV.